Gambaran Pengetahuan Lansia Penderita Stroke Berdasarkan Karakteristik Di Puskesmas Sialang Buah Tahun 2021 - Indra Hizkia P; Tresa Ernika Anglina Sitorus (Program Studi Akuntansi IKOPIN, 2022)
Stroke is a symptom that occurs due to impaired blood circulation in the brain. According to a report by the World Health Organization, 15 million people worldwide suffer a stroke every year. Stroke is a disease that is very vulnerable to the elderly. To determine the knowledge of elderly stroke patients based on age, gender, education and occupation at the Silang Buah Public Health Center in 2021. Method using descriptive The population in this study were 220 elderly stroke patients and the number of respondents was 69 people with consecutive sampling technique. The research instrument used a questionnaire to describe the knowledge of elderly stroke patients based on characteristics. The results of the study: most of the knowledge is sufficient with the number of respondents 40 people (58.0 %). Conclusion The knowledge of the elderly with stroke based on the characteristics at the Sialang Buah Health Center in 2021 is mostly sufficient, influenced by age and education factors. It is recommended to health workers to increase health education to the elderly about stroke, because many have sufficient knowledge about strokeStroke is a symptom that occurs due to impaired blood circulation in the brain. According to a report by the World Health Organization, 15 million people worldwide suffer a stroke every year. Stroke is a disease that is very vulnerable to the elderly. To determine the knowledge of elderly stroke patients based on age, gender, education and occupation at the Silang Buah Public Health Center in 2021. Method using descriptive The population in this study were 220 elderly stroke patients and the number of respondents was 69 people with consecutive sampling technique. The research instrument used a questionnaire to describe the knowledge of elderly stroke patients based on characteristics. The results of the study: most of the knowledge is sufficient with the number of respondents 40 people (58.0 %). Conclusion The knowledge of the elderly with stroke based on the characteristics at the Sialang Buah Health Center in 2021 is mostly sufficient, influenced by age and education factors. It is recommended to health workers to increase health education to the elderly about stroke, because many have sufficient knowledge about stroke